RP-HPLC Method Development for Simultaneous Estimation of Azilsartan Medoxomil and Chlorthalidone In Pharmaceutical Formulations - Amol Kakde; Neha Jain (Asian Journal of Pharmaceutical Research and Development, 2025)
Simple, accurate, economical and reproducible RP-HPLC method for simultaneous estimation of two component drug mixture AzilsartanMedoxomil and Chlorthalidone in combined tablet dosage form has been developed. Developed HPLC method is reversed phase chromatographic method using Inertsil C18 column and gradient mobile phase, detection of eluent was carried out using PDA detector at a flow rate of 1.2ml/ min. Forced degradation studies under various stress conditions, including hydrolysis, oxidation, thermal, humidity, and photolytic degradation, were performed. The developed method was validated in terms of specificity, linearity, precision, intermediate precision, accuracy, robustness and solution stability. The linearity was observed in concentration range of 12.5 ppm to 37.5 ppm for AzilsartanMedoxomil and from 3.5 ppm to 22.7ppm for Chlorthalidone. Results of analysis were validated statistically and by recovery studies. The proposed RP-HPLC method achieved satisfactory resolution between AzilsartanMedoxomil and Chlorthalidone. It can be used for determination of AzilsartanMedoxomil in drug substance and pharmaceutical preparation. Thismethod is suitable for routine quality control and stability testing of AzilsartanMedoxomil and Chlorthalidone in pharmaceutical formulations.